Pengembangan Media Pembelajaran Interaktif Unsur Warna dalam Desain Grafis - Ghama Yaskara Luli; Arip Mulyanto; Ahmad Azhar Kadim; Dian Novian; Mukhlisulfatih Latief; Jemmy A. Pakaja (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to develop an Android-based interactive learning media on the topic of color elements in graphic design and to determine its feasibility level. The method used was Research and Development (R&D) with the Four-D (4D) model, which consists of the stages of define, design, develop, and disseminate. The subjects of this study were tenth-grade students of the Computer and Network Engineering (TKJ) program at SMK Negeri 1 Batudaa. Data were collected through questionnaires involving media experts, material experts, and student responses. The results showed that the developed learning media achieved a high level of feasibility, with instrument validation results of 77% (feasible), media validation of 95% (very feasible), and material validation of 100% (very feasible). In addition, the student response test results showed a percentage of 82%, which falls into the very feasible category. This learning media is equipped with materials, videos, simple simulations, and interactive quizzes that can increase students’ interest and understanding. Therefore, the developed interactive learning media is considered feasible to be used as an alternative in graphic design learning.